2006
DOI: 10.1182/blood-2005-05-1809
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling the regulation of iron metabolism during erythroid differentiation to ensure efficient heme biosynthesis

Abstract: Terminal erythropoiesis is accompanied by extreme demand for iron to ensure proper hemoglobinization. Thus, erythroblasts must modify the "standard" posttranscriptional feedback regulation, balancing expression of ferritin (Fer; iron storage) versus transferrin receptor (TfR1; iron uptake) via specific mRNA binding of iron regulatory proteins (IRPs). Although erythroid differentiation involves high levels of incoming iron, TfR1 mRNA stability must be sustained and Fer mRNA translation must not be activated bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 82 publications
3
68
1
1
Order By: Relevance
“…The ALAS gene was differently expressed between flounder populations in both gill and liver tissues and ALAS has previously been shown to be highly important for the iron/heme biosynthesis (Astner et al, 2005) primarily catalyzing the first step of heme biosynthesis (Schranzhofer et al, 2006). The observation of constitutive intraspecific variation in expression of ALAS across several tissues underlines the functional importance of the observed variation.…”
Section: Discussionmentioning
confidence: 73%
“…The ALAS gene was differently expressed between flounder populations in both gill and liver tissues and ALAS has previously been shown to be highly important for the iron/heme biosynthesis (Astner et al, 2005) primarily catalyzing the first step of heme biosynthesis (Schranzhofer et al, 2006). The observation of constitutive intraspecific variation in expression of ALAS across several tissues underlines the functional importance of the observed variation.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, Martinez-Medellin and Schulman 27 observed that, when rabbit reticulocytes were treated with 59 Fe-Tf, radioiron was apparent only in either hemoglobin or a stromal-bound fraction. Furthermore, the recent study by Schranzhofer et al 49 showed a decrease in the sensitivity of the cytosolic iron regulatory proteins to Tf-derived iron in erythroid progenitors, as the cells differentiate. Together, these results are consistent with our model of iron delivery in Hb-synthesizing cells whereby the metal does not enter the cytosol, but is rapidly shuttled from endosome to the site of heme synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IRPs play a prominent role in adjusting protoporphyrin synthesis to transferrin-bound iron availability in erythroblasts, as suggested by the zebrafish anaemia induced by sustained activation of IRP1 [3]. But synthesis of proteins participating in iron homoeostasis does not always fit with the IRE-IRP model of regulation along differentiation of the lineage [4,5]. Other regulatory events, including transcriptional ones, may combine with, or supersede, the translational control carried out by IRP.…”
Section: Introductionmentioning
confidence: 99%